2002
DOI: 10.1093/aje/kwf048
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Invasive Epithelial Ovarian Cancer: Results from a Swedish Case-Control Study

Abstract: This case-control study evaluated reproductive and other factors in relation to epithelial ovarian cancer (EOC) risk. Between 1993 and 1995, the authors recruited 655 EOC cases and 3,899 population controls aged 50-74 years who were born in and residents of Sweden. Data were collected through mailed questionnaires. Odds ratios were estimated by unconditional logistic regression. Parity reduced EOC risk (odds ratio = 0.61, 95% confidence interval (CI): 0.46, 0.81) for uniparous compared with nulliparous women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
195
2
15

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(238 citation statements)
references
References 59 publications
(103 reference statements)
26
195
2
15
Order By: Relevance
“…5 For most sites, our findings are moderately in accordance with the results from literature. [2][3][4][5][6][7][11][12][13] Our results show that from 5366 patients diagnosed with a malignant primary epithelial ovarian tumor, 142 cases also manifested a concurrent endometrial malignancy (2.6%). Sheu et al report six cases from 421 ovarian cancer patients, who were also diagnosed with a synchronously endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 For most sites, our findings are moderately in accordance with the results from literature. [2][3][4][5][6][7][11][12][13] Our results show that from 5366 patients diagnosed with a malignant primary epithelial ovarian tumor, 142 cases also manifested a concurrent endometrial malignancy (2.6%). Sheu et al report six cases from 421 ovarian cancer patients, who were also diagnosed with a synchronously endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1 The prognosis is poor with 5-year survival rates of about 40%. 2 Survival for women with ovarian cancer has improved, such that the occurrence of second malignant neoplasms is surfacing. One study reported increased risk of second primary ovarian cancer in women diagnosed previously with cancer of different sites.…”
mentioning
confidence: 99%
“…Of all proposed risk factors, ovulation has received the widest attention. The theory that persistent ovulation increases ovarian cancer incidence was first proposed by Fathalla in 1971(Fathalla, 1971Fathalla, 1972) and has been supported by numerous studies demonstrating that a reduction in ovulatory events by pregnancy and/or oral contraceptive decreases EOC risk (Riman et al, 2002;Risch et al, 1994;Risch et al, 1983;Titus-Ernstoff et al, 2001;Whittemore et al, 1992). Advocates of this so-called incessant ovulation hypothesis argue that repeated rupture of the ovarian surface during ovulation and subsequent repair by OSE proliferation may increase the frequency at which mutations arise.…”
Section: Disease Etiologymentioning
confidence: 95%
“…These authors suggested the hypothesis that there is a etiopathogeny of ovarian cancer related to retrograde blood flow and other substances (such as talcum powder, for example) through the Fallopian tubes. 17 …”
Section: Ovarian Cancermentioning
confidence: 99%
“…However, a positive relationship between breastfeeding and reduced incidence of diseases such as breast cancer, [1][2][3][4][5][6][7][8][9][10][11][12][13] certain types of ovarian cancer, 10,[14][15][16][17] and bone fractures, mainly hip fractures caused by osteoporosis. 10,[18][19][20][21][22] There are also evidences that breastfeeding reduces the risk of death from rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%